2017
DOI: 10.1007/s11695-017-3014-x
|View full text |Cite
|
Sign up to set email alerts
|

Rare Entities of Histopathological Findings in 755 Sleeve Gastrectomy Cases: a Synopsis of Preoperative Endoscopy Findings and Histological Evaluation of the Specimen

Abstract: Both preoperative endoscopic assessment and postoperative histopathological examination of the specimen are mandatory in LSG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
2
11
1
2
Order By: Relevance
“…Neoplasia was a rare finding in both our study and previous studies. While the frequency of GIST ranges from 0 to 1.2% (10,11,15,16,19,20,25) in the literature, we found 0.44% in our series. We detected all of these patients during the surgery and there was no need to change the treatment and follow-up protocol both in the surgical technique and in the postoperative period.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Neoplasia was a rare finding in both our study and previous studies. While the frequency of GIST ranges from 0 to 1.2% (10,11,15,16,19,20,25) in the literature, we found 0.44% in our series. We detected all of these patients during the surgery and there was no need to change the treatment and follow-up protocol both in the surgical technique and in the postoperative period.…”
Section: Discussioncontrasting
confidence: 60%
“…In most of the previously published series, it was reported that upper gastrointestinal system endoscopy was performed preoperatively, and fewer studies reported that there were few or no endoscopic examinations (7)(8)(9)(10)(11). However, this issue is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, pre-malignant lesions identified in LSG specimens across 11 studies varied from 4.1 to 33.2% [10,18,[36][37][38][39][40][41][42][43][44]. However, across these 11 abovementioned studies, there was zero actual malignancy reported, despite that these studies were undertaken in a wide variety of geographical areas worldwide with different risk of gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even with our 7.5% pre-malignant lesions identified in LSG specimens, and with the huge number of LSG procedures undertaken worldwide, such current lack of the evidence base renders us unable to extrapolate in any way the potential number of patients with pre-malignant lesions that would actually turn malignant or whether such numbers would be high and alarming or otherwise. Hence, there exists much debate regarding the role of routine histopathological examination of LSG specimens [10,18,[36][37][38][39][40][41][42][43][44], and some authors have suggested that histopathological examination of LSG specimens is to be done when intraoperative macroscopic pathology is observed [10,18,43]. Future research would benefit from addressing these points.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Yardimci et al [ 18 ] evaluated 755 specimens and found neoplasms in 4 (0.5%) cases. Canil et al [ 19 ] analyzed 925 cases in a 5-year span with a 0.3% rate of neoplasms.…”
Section: Discussionmentioning
confidence: 99%